Evaluation of heated air jet on pulp chamber temperature at different steps of the restorative protocol (Research, Society and Development, 2021)
Objectives: Evaluate of the heated air jet temperature (T) in the pulp chamber on cavity 5 depths and photoactivation stages for a bulk fill resin restorative protocol is evaluated. Methods: Class I cavity preparations were conducted at different depths (n = 8) through two protocols for adhesive volatilization (23 °C and 40 °C) and cavities were restored with the Filtek Bulk Fill resin. The pulp chamber temperature variation was evaluated at four steps (times) during the restorative protocol: I (initial), V (after volatilization), A (after photoactivation of the adhesive), and C (after photoactivation of the composite resin). To verify the assumptions of the normality of the errors and homoscedasticity, the Shapiro Wilk and Levene tests were conducted. Subsequently, two-way and three-way analysis of variance was carried out, followed by Tukey's post-hoc analysis (α = 0.05). Results: The maximum T at the different restorative steps, regardless of the volatilization protocol and cavity depth, was as follows: I (36.8 °C) = V (36.9 ºC) < A (37.2 °C) = R (37.8 ºC) (p